Using multi-agent systems and consensus methods for information retrieval in internet. (21st August 2007) - Sliwko, Leszek; Nguyen, Ngoc Thanh
The paper presents a consensus-based approach utilised within a multi-agent system, which assists users in retrieving information from the internet. In this system, consensus methods are applied for reconciling inconsistencies among independent answers generated by agents (using various search engines) for a given query. AI methods have been developed to allow the agent's self-improvement. The proposed agent system has been implemented and the initial experiment results are presented here.